Analisis Aspek Normatif dan Sosiologis Pengguna Cadar: Studi di Ma’had Al Birr Unismuh Makassar - Rusdin Rusdin; Abd. Rauf Muhammad Amin; St. Halimang (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the importance of understanding the niqab (face veil) as a religious symbol and an identity marker for Muslim women, which continues to spark public debate in Indonesia. The niqab is often viewed from various perspectives—religious, cultural, social, and political—making it a controversial topic. These differing viewpoints highlight the need for a deeper exploration of the meaning and practice of wearing the niqab, especially within Islamic higher education institutions. The study aims to examine both the normative and sociological aspects of niqab use among female students at Ma’had Al-Birr, Muhammadiyah University (Unismuh) Makassar. This institution is known for having a significant number of students who wear the niqab, each with different backgrounds and motivations, ranging from theological beliefs to personal convictions and environmental influences. The research employs a descriptive qualitative method with a field-based approach. It combines normative Islamic theological perspectives with sociological analysis, using data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that students perceive the niqab not merely as a religious obligation to cover one's aurat (parts of the body that should be concealed), but also as a symbol of piety, honor, obedience, and personal ijtihad (independent reasoning) in practicing Islamic teachings. An inclusive campus environment supports these students in engaging freely in both academic and social activities. However, challenges still arise, particularly in the form of stereotypes and perceptions of exclusivity that some individuals associate with niqab wearers. These misconceptions underscore the importance of cross-perspective understanding in addressing this phenomenon. This study is expected to contribute to the development of campus policies that support freedom of expression, uphold mutual respect, and promote a more inclusive, open, and tolerant atmosphere within Islamic higher education institutions—one that embraces the diversity of religious practices and encourages respectful coexistence.